Experiencias en españa sobre el tratamiento laboral del coronavirus (covid-19) - Solesio Jofre de Villegas, Antonio (2021)
On March 11, 2020, the World Health Organization (WHO) declared the Coronavirus COVID-19 Pandemic, setting a starting point for the responses that each state must articulate within their respective policy areas. In Spain, the process began on March 14, 2020 with the formal declaration of the State of Alarm. Since then, varied measures have been aligned in different fields. These measures share a common denominator and primary objective: To strike a balance between overcoming the health crisis and protecting citizens from the adverse effects of the crisis. In this context, the social legislation package the Spanish Government has already scheduled to tackle this situation becomes highly important. Thus, the main objective of this paper is to present a descriptive analysis for the above-mentioned social actions and their dynamic implementation, as conditioned by the future development of the health situation itself.